Forecast sales volume of aviation fuel in Jakarta using ARIMA Method to support inventory control - Setiyawan, Ary Putra; Wibowo, Wahyu; Atok, R. Mohamad (Indonesian Journal of Multidisciplinary Science, 2024)
The civil aviation industry in Indonesia experienced a significant increase from 2009-2018. The increase occurred in passenger and cargo activities. However, the situation changed drastically when the Covid-19 pandemic occurred throughout the world in 2019. PT xyz as a company need to adapt and optimize the business process. Inventory management is something that can be optimized. The aim of this research was to forecast aviation fuel demand in Jakarta and utilize the forecast result as a basis for inventory management. This research utilizes time series data on aviation fuel sales to determine demand estimates for the following month. The method used to forecast is the Autoregressive Integrated Moving Average. Furthermore, the forecast data is combined with information on storage capacity and historical data on product supply arrivals as input data in calculating safety stock to obtain more economical inventory management. The result of this research is that the best forecast avtur demand in Jakarta is using Arima (1,1,1). Safety inventory calculation based on demand forecasting with 90% cycle service level for Jakarta is 42,495 kiloLiter and PT xyz still can reduce products in their storage worth IDR. 341.8 M in Jakarta to maintain the same cycle service level.